Nationalism In Realizing The Goals Of The National Pillars: Challenges, Creative And Innovative Ideas That Youth Should Have - Rio Armanda Agustian (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2023)
The importance of understanding the four pillars of nationalism in the life of the nation and state for today's young generation, especially nationalism, is so that youth have the values of national insight and patriotism in themselves so that they have a sense of responsibility in providing the best for their country. To fulfill this, the youth must have creative and innovative ideas and ideas in building the nation and state. The four pillars of nationalism consisting of Pancasila, Undang-Undang Dasar Tahun 1945, Bhinneka Tunggal Ika and Negara Kesatuan Republik Indonesia have the value of moral principles to achieve the life of an independent, sovereign, just and prosperous Indonesian nation as stated in the goals of the Nation and state in the UUD Negara Republik Indonesia tahun 1945. This is reflected that these 4 pillars have important purposes and meanings and are useful for current and future generations. It should be realized by today's youth that the younger generation must be required to face all the challenges that exist today, namely globalization which is very extraordinary in affecting the sense of nationalism of youth. We can also see the many law violations that occur committed by youth as a result of the lack of actualizing the values of the 4 pillars of nationalism in family life, society and the nation and state. As for other efforts that can be made to foster a sense of nationalism, namely by making a work with the theme of love for the country, heroism, and so on that is national in nature so that in the process of making the work the younger generation will be reminded of the struggles of the nation's heroes before and thus a sense of nationalism in themselves will be embedded and grow in their souls. Related to the above, there are actually many positive activities that can be carried out by young people to build their country so that the sense of nationalism can be maintained.